Future is urban : livability, resilience & resource conservation : proceedings of the International Conference on Future is Urban (ICFU 21), December 16-18, 2021, Ahmedabad, India /: livability, resilience & resource conservation : proceedings of the International Conference on Future is Urban (ICFU 21), December 16-18, 2021, Ahmedabad, India. (2023) - Unknown
No abstract available